The Effect of Self-compassion on the Anxiety Level of Students During the Final Project Period - Sudirman, Nur Andini; Sari, Famella (Yayasan Sinergi Kawula Muda, 2023)
This qualitative study investigates the relationship between anxiety and self-compassion among undergraduate and graduate students working on capstone projects in Indonesian higher education. In semi-structured interviews, fifteen participants discussed their experiences, offering subtle insights on coping tactics, outside pressures, and methods for developing self-compassion during the final project phase. Thematic analysis sheds light on the critical function that self-compassion plays as a buffer against anxiety, emphasizing the value of self-kindness, acknowledging our common humanity, and practicing mindfulness in building emotional resilience. The results highlight how crucial it is to support students' academic success and well-being in higher education settings by destigmatizing mental health issues and encouraging the cultivation of self-compassion.